Core inflation: Robust common trend model forecasting - Ajax Reynaldo Bello Moreira; Hélio dos Santos Migon (Institute for Applied Economic Research (ipea), 2015)
The monetary authorities need a future measure of inflation trend to keep on tracking the inflation on target. Many alternatives of the core inflation measure have appeared in the recent literature pretending to avoid the deficiencies of the usual headline inflation index as a predictor. This price index is defined as some weighted average of the individual price change of a list of goods and services. To use it as the future inflation indicator is criticized in the literature, as far as the products are heterogeneous in respect to the variability and some of the involved prices have relevant seasonal movements. A multivariate model including simultaneously the seasonal effects of each component of the price index and a common trend - the core inflation - will be developed in this paper. The model will be phrased as a dynamic model and a robust sequential filter will be introduced. The posterior and predictive distributions of the quantities of interest will be evaluated via stochastic simulation techniques, MCMC - Monte Carlo Markov Chain. Different models will be compared using the minimum posterior predictive loss approach and many graphical illustrations will be presented.
Keywords: 330; Core inflation; Robust Kalman Filter; Common Trend; Influence function